2020
DOI: 10.1136/bmjopen-2019-032748
|View full text |Cite
|
Sign up to set email alerts
|

Depression among adult patients with primary brain tumour: a cross-sectional study of risk factors in a low–middle-income country

Abstract: ObjectiveThe prevalence of depression among patients with primary brain tumour ranges from 15% to 40% globally. Several individual and clinical factors contribute to the development of depression. However, their association with depression in Pakistani setting has not yet been assessed. Thus, we aim to study the factors associated with depression among adult patients with primary brain tumour at a tertiary care hospital in Karachi, Pakistan.Study designA prospective cross-sectional study.SettingThis study was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 32 publications
(43 reference statements)
0
5
0
Order By: Relevance
“…In the study conducted by Pidani et al [ 24 ] in Pakistan, 51 patients with brain tumors were examined. The findings indicated that depression is a common occurrence among individuals with primary brain tumors and directly affects their functional status, which aligns with the results of the current investigation.…”
Section: Discussionmentioning
confidence: 99%
“…In the study conducted by Pidani et al [ 24 ] in Pakistan, 51 patients with brain tumors were examined. The findings indicated that depression is a common occurrence among individuals with primary brain tumors and directly affects their functional status, which aligns with the results of the current investigation.…”
Section: Discussionmentioning
confidence: 99%
“…[ 18 , 19 ] Furthermore, a patient’s mental health problems worsen further during surgery and treatment. [ 20 , 21 ] Other cohort and clinical studies have also shown that depression is an important prognostic factor for the survival of glioma patients. Compared to HGG group without depression, HGG patients with depression have shorter overall survival.…”
Section: Introductionmentioning
confidence: 99%
“…Patients with primary brain tumors (PBTs) often suffer from clinically significant psychological distress [ 1 ], the levels of which are higher than that experienced by patients suffering from most other types of malignancies [ 2 ]. Common mental health problems include depression, anxiety, stress, adjustment disorder and post-traumatic stress disorder, in addition to mental and emotional fatigue [ 2 , 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Findings related to QoL, and its associated psychosocial factors, are likely to differ in Pakistan due to a unique economic, social, and cultural landscape [ 11 ]. A study in Pakistan conducted in 2020 showed that almost 40% of patients with PBTs have depressive symptoms, which were associated independently with social factors such as employment status [ 3 ]. As survivorship of patients with PBTs increases as a function of rapidly evolving therapies, QoL is being increasingly measured as an additional endpoint alongside traditional clinical outcomes in disease management and clinical trials [ 12 ].…”
Section: Introductionmentioning
confidence: 99%